Genetic modification of western wheatgrass (Pascopyrum smithii) for the phytoremediation of RDX and TNT - Long Zhang; Elizabeth L. Rylott; Neil C. Bruce; Stuart E. Strand (Planta, 2019)

Ammonia‐oxidizing bacteria are the primary N 2 O producers in an ammonia‐oxidizing archaea dominated alkaline agricultural soil - Kelley A. Meinhardt; Nejc Stopnisek; Manmeet W. Pannu; Stuart E. Strand; Steven C. Fransen; Karen L. Casciotti; David A. Stahl (Environmental Microbiology, 2018)
Summary Most agricultural N 2 O emissions are a consequence of microbial transformations of nitrogen (N) fertilizer, and mitigating increases in N 2 O emission will depend on identifying microbial sources and variables influencing their activities. Here, using controlled microcosm and field studies, we found that synthetic N addition in any tested amount stimulated the production of N 2 O from ammonia‐oxidizing bacteria (AOB), but not archaea (AOA), from a bioenergy crop soil. The activities of these two populations were differentiated by N treatments, with abundance and activity of AOB increasing as nitrate and N 2 O production increased. Moreover, as N 2 O production increased, the isotopic composition of N 2 O was consistent with an AOB source. Relative N 2 O contributions by both populations were quantified using selective inhibitors and varying N availability. Complementary field analyses confirmed a positive correlation between N 2 O flux and AOB abundance with N application. Collectively, our data indicate that AOB are the major N 2 O producers, even with low N addition, and that better‐metered N application, complemented by selective inhibitors, could reduce projected N 2 O emissions from agricultural soils.

Phytodetoxification of TNT by transplastomic tobacco (Nicotiana tabacum) expressing a bacterial nitroreductase - Long Zhang; Elizabeth L. Rylott; Neil C. Bruce; Stuart E. Strand (Plant Molecular Biology, 2017)

Agricultural land usage transforms nitrifier population ecology - Anthony D. Bertagnolli; Dylan McCalmont; Kelley A. Meinhardt; Steven C. Fransen; Stuart Strand; Sally Brown; David A. Stahl (Environmental Microbiology, 2016)
Summary Application of nitrogen fertilizer has altered terrestrial ecosystems. Ammonia is nitrified by ammonia and nitrite‐oxidizing microorganisms, converting ammonia to highly mobile nitrate, contributing to the loss of nitrogen, soil nutrients and production of detrimental nitrogen oxides. Mitigating these costs is of critical importance to a growing bioenergy industry. To resolve the impact of management on nitrifying populations, amplicon sequencing of markers associated with ammonia and nitrite‐oxidizing taxa (ammonia monooxygenase‐ amo A , nitrite oxidoreductase‐ nxr B , respectively) was conducted from long‐term managed and nearby native soils in Eastern Washington, USA . Native nitrifier population structure was altered profoundly by management. The native ammonia‐oxidizing archaeal community (comprised primarily by N itrososphaera sister subclusters 1.1 and 2) was displaced by populations of N itrosopumilus , N itrosotalea and different assemblages of N itrososphaera (subcluster 1.1, and unassociated lineages of N itrososphaera ). A displacement of ammonia‐oxidizing bacterial taxa was associated with management, with native groups of Nitrosospira (cluster 2 related, cluster 3A.2) displaced by N itrosospira clusters 8B and 3A.1. A shift in nitrite‐oxidizing bacteria ( NOB ) was correlated with management, but distribution patterns could not be linked exclusively to management. Dominant nxrB sequences displayed only distant relationships to other NOB isolates and environmental clones.

Mammalian cytochrome CYP2E1 triggered differential gene regulation in response to trichloroethylene (TCE) in a transgenic poplar - Jun Won Kang; Hui-Wen Wilkerson; Federico M. Farin; Theo K. Bammler; Richard P. Beyer; Stuart E. Strand; Sharon L. Doty (Functional & Integrative Genomics, 2010)

Analysis and comparison of the microbial community structures of two enrichment cultures capable of reductively dechlorinating TCE and cis ‐DCE - April Z. Gu; Brian P. Hedlund; James T. Staley; Stuart E. Strand; H. David Stensel (Environmental Microbiology, 2004)
Summary In order to study the effect of different chloroethenes (electron acceptors) on the bacterial composition of dechlorinating communities, two reductive dechlorinating enrichment cultures were developed that were able to reduce trichloroethene (TCE) and cis ‐1,2‐dichloroethene ( cis ‐DCE) to ethene using hydrogen as electron donor, respectively. The inoculum for the cultures was material from a methanogenic fluidized bed reactor (FBR), which was originally seeded with digester sludge and showed a stable capacity for tetrachloroethene (PCE) reduction to ethene for over six years. Molecular methods were used to determine and compare the microbial communities of these two enrichment cultures. A clone library of bacterial 16S rRNA genes was generated for each enrichment. The clones were screened into different groups by restriction fragment length polymorphism (RFLP) analysis using two different four base pair recognition restriction enzymes. A total of 12 sequence types were identified by phylogenetic analysis of nearly complete 16S rDNA sequences (∼1450 bp). The sequences were affiliated with six recognized phyla of the domain Bacteria: Firmicutes (low G+C Gram‐positives), Chloroflexi (green non‐sulphur bacteria), Actinobacteria (high G+C Gram‐positives), Bacteroidetes (Cytophaga‐Flexibacter‐Bacteroides), Nitrospira and Spirochaetes. The results led to the identification of an organism closely related to Dehalococcoides ethenogenes to be the presumptive dechlorinator in both enrichments. Different electron acceptors affected the bacterial diversity and the community profiles of the two enrichments. Most of the sequences identified in our dechlorinating enrichments shared high similarities with sequences previously obtained from other enriched dechlorinating cultures and chlorinated‐compound‐contaminated sediments or aquifers, suggesting these bacteria may have direct or indirect roles in reductive dechlorination.

Mechanism of aerobic transformation of carbon tetrachloride by poplar cells - Xiaoping Wang; Milton P. Gordon; Stuart E. Strand (Biodegradation, 2002)

Anaerobic transformation of 1,1,1-trichloroethane by municipal digester sludge - Chun Chen; Bhasker S. Ballapragada; Jaakko A. Puhakka; Stuart E. Strand; John F. Ferguson (Biodegradation, 1999)